Rancang Bangun Sistem Informasi Pemesanan Percetakan Berbasis Website di Fabian Percetakan Cicalengka - Tonton Taufik Rachman; Dini Andini; Hendra Gunawan (Ma'soem University, 2022)
The problems that occur at Fabian Printing are that orders must come directly to the location, recording is still manual using excel and promotions are still limited. The method used in this study is the OOAD (Object Oriented Analysis and Design) system development method with the RUP (Rational Unified Process) model and the development tool in the form of UML (Unified Modeling Language). With the design of this website-based printing ordering information system to facilitate the administration in recording transactions and backing up data automatically and can improve the time service, information and product ordering provided at Fabian Printing Cicalengka which can be done online.